Effects of build orientation and heat treatment on microstructure, mechanical and corrosion properties of Al6061 aluminium parts built by cold spray additive manufacturing process. (15th August 2021) - Hutasoit, Novana; Javed, Muhammad Awais; Rashid, Rizwan Abdul Rahman; Wade, Scott; Palanisamy, Suresh
Highlights: Bulk samples in the as-deposited state showed very poor mechanical properties due to low inter-particle bond strength. Horizontally-built samples showed lowest pitting corrosion resistance compared to other samples. Considerable anisotropy in both mechanical as well as corrosion properties were observed for samples printed in two different orientations. Particle shape generated by cold spray process exhibits an influence on the strength of horizontally and vertically build deposits. Post-build heat treatment significantly improved the strength, ductility, and corrosion resistance of the CSAM parts. Abstract: Aluminium 6061 alloy (Al6061) is one of the widely used materials in the aluminium alloy family for structural applications owing to its high strength-to-weight ratio and high corrosion resistance. Al6061 components are traditionally manufactured using conventional processes such as casting, forging, rolling, and machining, which typically involved high scrap/waste generation. However, with the advent of advanced additive manufacturing (AM) processes, there is an opportunity to reconsider component design to near-net shapes with reduced material wastage. Although mechanical and corrosion properties of Al6061 fabricated with conventional processes is well understood, very little information is known about AMed Al6061. This study investigates the effect of build orientation and heat treatment on the mechanical and corrosion properties of Al6061 samples manufactured by cold spray additive manufacturing (CSAM) process. To the best of the authors' knowledge, this work is the first to explore both the mechanical and corrosion properties of Al6061 alloy print-parts fabricated using this unique CSAM system. Due to the lack of metallurgical bonding between powder particles, as-deposited samples - regardless of their build orientation, exhibited lower strength and ductility compared to the wrought counterparts. Particle shape generated by cold spray process exhibits an influence on the strength of horizontally and vertically build deposits. Expectedly, heat treatment significantly improved the mechanical properties by inducing metallurgical bonding at prior particle boundaries. As for corrosion resistance, horizontally-built samples exhibited the highest pit depth and pit penetration rate compared to the other conditions, which suggested a higher susceptibility to pitting corrosion owing to more strain-hardened particle sites available for corrosive attack. Heat treatment on as-deposited samples produced strain-free grains; thus, eliminating areas prone to corrosive environmental attack, leading to improvement in pitting corrosion resistance. Investigating post-processing heat treatment is crucial to improve the mechanical properties of as-deposited samples to a level similar to the ones of wrought condition. This research work is essential for selecting the correct processing routes and their parameters to manufacture components exposed to corrosive environments. Graphical abstract: Image, graphical abstract